2018
DOI: 10.1016/j.cmi.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and analytical evaluation of the new Aptima Mycoplasma genitalium assay, with data on M. genitalium prevalence and antimicrobial resistance in M. genitalium in Denmark, Norway and Sweden in 2016

Abstract: Both transcription-mediated amplification (TMA)-based MG assays had a highly superior sensitivity compared to the mgpB qPCR. The prevalence of MG and azithromycin resistance was high. Validated and quality-assured molecular tests for MG, routine resistance testing of MG-positive samples and antimicrobial resistance surveillance are crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
6
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 33 publications
(32 reference statements)
11
69
6
3
Order By: Relevance
“…In this study, we validated the performance characteristics of four TMA NAAT assays for the detection of ribosomal RNAs from M. genitalium. We found that these assays are sensitive and specific for the detection of multiple stains of M. genitalium and have Similarly to NAATs designed to detect other sexually transmitted infections such as Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis, the detection of rRNA of M. genitalium affords a particularly sensitive method for detecting the organism in vivo, leading to improved clinical diagnosis of M. genitalium infection compared to that with NAATs that target genomic DNA of the organism (20)(21)(22). This difference in relative test clinical sensitivity may be due to the disparity between genomic DNA and rRNA content in the cell (i.e., a single DNA genome versus an estimated hundreds to thousands of rRNA copies per cell) (29), enabling the detection of low titers of M. genitalium in patient specimens (30,31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we validated the performance characteristics of four TMA NAAT assays for the detection of ribosomal RNAs from M. genitalium. We found that these assays are sensitive and specific for the detection of multiple stains of M. genitalium and have Similarly to NAATs designed to detect other sexually transmitted infections such as Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis, the detection of rRNA of M. genitalium affords a particularly sensitive method for detecting the organism in vivo, leading to improved clinical diagnosis of M. genitalium infection compared to that with NAATs that target genomic DNA of the organism (20)(21)(22). This difference in relative test clinical sensitivity may be due to the disparity between genomic DNA and rRNA content in the cell (i.e., a single DNA genome versus an estimated hundreds to thousands of rRNA copies per cell) (29), enabling the detection of low titers of M. genitalium in patient specimens (30,31).…”
Section: Discussionmentioning
confidence: 98%
“…The TMA-based Aptima Mycoplasma genitalium assay (AMG) is an FDA-cleared (510k number DEN180047) in vitro diagnostic (IVD) test for the detection of 16S rRNA from M. genitalium. Application of the AMG IVD assay outside the United States has been described (20)(21)(22). In the present study, we developed and optimized three additional alternate (Alt) TMA assays, Alt TMA-1, Alt TMA-2, and Alt TMA-3, to capture, amplify, and detect unique regions of 16S rRNA (Alt TMA-1) or 23S rRNA (Alt TMA-2 and Alt TMA-3) of M. genitalium.…”
Section: Methodsmentioning
confidence: 99%
“…This might explain the difference in sensitivity of the MgPa assay and Mg Macrolide R assay. Using RNA as input obviously increases the sensitivity when compared to DNA as used in our RTN-qPCR sequencing method and is employed by Aptima PCRs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Распространенность резистентных мутаций для азитромицина и моксифлоксацина составляла 41,4 (17,7-56,6) и 6,6% (4,1-10,2%) соответственно. Также в этих странах была обнаружена множественная лекарственная устойчивость (2,7; 1,1-4,2%) [59].…”
Section: проблема антибиотикорезистентности M Genitaliumunclassified